A complex comprising C15ORF41 and Codanin-1: the products of two genes mutated in congenital dyserythropoietic anaemia type I (CDA-I). Issue 10 (28th May 2020) - Shroff, Maithili; Knebel, Axel; Toth, Rachel; Rouse, John
Abstract : Congenital dyserythropoietic anaemia (CDA) type I is a rare blood disorder characterised by moderate to severe macrocytic anaemia and hepatomegaly, with spongy heterochromatin and inter-nuclear bridges seen in bone marrow erythroblasts. The vast majority of cases of CDA type I are caused by mutations in the CDAN1 gene. The product of CDAN1 is Codanin-1, which interacts the histone chaperone ASF1 in the cytoplasm. Codanin-1 is a negative regulator of chromatin replication, sequestering ASF1 in the cytoplasm, restraining histone deposition and thereby limiting DNA replication. The remainder of CDA-I cases are caused by mutations in the C15ORF41 gene, but very little is known about the product of this gene. Here, we report that C15ORF41 forms a tight, near-stoichiometric complex with Codanin1 in human cells, interacting with the C-terminal region of Codanin-1. We present the characterisation of the C15ORF41–Codanin-1 complex in humans in cells and in vitro, and demonstrate that Codanin-1 appears to sequester C15ORF41 in the cytoplasm as previously shown for ASF1. The findings in this study have major implications for understanding the functions of C15ORF41 and Codanin-1, and the aetiology of CDA-I.